PENGARUH TERAPI MUSIK TRADISIONAL CINA TERHADAP KESEPIAN PADA LANSIA DI PANTI JOMPO YAYASAN GUNA BUDI BAKTI KELURAHAN MARTUBUNG KECAMATAN MEDAN LABUHAN KOTA MEDAN TAHUN 2019 - Arlis, Arlis (Jurnal Keperawatan Priority, 2019)
Loneliness in the elderly is a common thing where they feel feelings of isolation, exclusion, lack of attention from those around them, isolated from others. Traditional music is ethnic music originating from each region and even tribe, this music has a regular rhythm so that it can create relaxation and optimal resting conditions. This study used the Quasi Experiment Design with the onegroup pre and post test design method. The purpose of this study was to determine the effect of traditional Chinese music therapy on loneliness in the elderly. The population in this study amounted to 70 people with a sample of 41 people using Purposive Sampling techniques. Data collection uses the Ucla Loneliness Scale Version 3 questionnaire. The results of the Paired Sample T-Test statistic obtained p-value 0,000 <0.05, which means that there is an influence of traditional Chinese music therapy on loneliness in the elderly. Based on the results of these studies, traditional Chinese music therapy can be used as an alternative to reduce loneliness.